1999
DOI: 10.1007/s004420050875
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition by mutualistic seed-parasitic pollinators and its effects on annual fitness of single- and multi-flowered host plants

Abstract: The balance of intimate relationships between plants and seed-eating pollinators can depend on pollinator behaviour in relation to floral characters, such as flower size and flower number. Here, we examined how pollinator oviposition in relation to these traits affected annual fitness (seed output) of single- and multi-flowered Trollius europaeus along altitudinal gradients in subarctic Sweden and the French Alps. Small flies (Chiastocheta spp.) pollinate T. europaeus and their larvae feed on developing seeds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Few cases of such extremely specific pollination mutualisms have been documented: the Ficus spp.-Agaonidae wasp (Bronstein, 1992;Anstett et al, 1996), the Yucca spp.-Tegeticula spp. moth (Powell, 1992), and the Trollius europaeus-Chiastocheta fly interactions (Pellmyr, 1989;Jaeger and Després, 1998;Hemborg and Després, 1999;Jaeger et al, 2000Jaeger et al, , 2001. In accordance with the cospeciation hypothesis, in the fig-fig wasp system, one plant species is usually associated with one pollinating insect species (Machado et al, 2001).…”
Section: Introductionmentioning
confidence: 56%
“…Few cases of such extremely specific pollination mutualisms have been documented: the Ficus spp.-Agaonidae wasp (Bronstein, 1992;Anstett et al, 1996), the Yucca spp.-Tegeticula spp. moth (Powell, 1992), and the Trollius europaeus-Chiastocheta fly interactions (Pellmyr, 1989;Jaeger and Després, 1998;Hemborg and Després, 1999;Jaeger et al, 2000Jaeger et al, , 2001. In accordance with the cospeciation hypothesis, in the fig-fig wasp system, one plant species is usually associated with one pollinating insect species (Machado et al, 2001).…”
Section: Introductionmentioning
confidence: 56%
“…including six populations sampled for 3 consecutive years (1995,1996,1997). Study sites represent a wide range of ecological conditions (Jaeger and Després 1998;Hemborg and Després 1999). This resulted in a total of 38 records, each representing a group of globeXowers sharing their pollinators, hereafter called a "population".…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest that seed eaters may exact considerable fitness penalties on plants, which should favour individuals whose floral traits reduce such predation. Previous studies have suggested a link between floral display and seed predation, for example in Ipomopsis aggregata (Polemoniaceae;Brody 1992;Brody and Mitchell 1997), Lathyrus vernus (Fabaceae;Ehrlén 1996), and Trollius europaeus (Ranunculaceae; Hemborg and Després 1999). Among the Asteraceae, it has been shown that the number of eggs laid by the weevil Rhinocyllus conicus in flowerheads of Cirsium vulgare and Silybum marianum is positively related to the capitulum diameter (Zwölfer and Preiss 1983).…”
Section: Introductionmentioning
confidence: 98%